Kualitas Penyajian Bahan Makanan Guna Meningkatkan Kualitas Gizi Anak Binaan di LPKA - Michael Bramulia Tarigan; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Providing adequate food for detainees, children and detainees in Detention Centers (Rutan), Special Child Development Institutions (LPKA), and Correctional Institutions (Lapas) is a service of the Ministry of Law and Human Rights to guarantee the basic rights of prisoners and children .